Salvador Sánchez Colín and the Extension Service of the State of Mexico: Agricultural Development and Green Revolution (1952-1957) - Gutiérrez Núñez, Netzahualcóyotl Luis (2023)
The article analyzes the organization and functioning of the first extension service in Mexico, which was established in the State of Mexico in 1952, within the government of the agronomy engineer Salvador Sánchez Colín. The research states that this institution, paramount for diffusing agricultural innovations of the so-called «green revolution», had three sources. The first one refers to one program of agricultural development built up by Sánchez between 1945 and 1951, which defined the crops-and-livestock activities that would be the target of streamlining. The second is related to previous experiences of agricultural extension in Mexico, with a particular interest in those of the National Corn Commission, which between 1949 and 1951 started projects of improved seeds and fertilizers diffusion. The third was the technical and financial support of the Mexican Agricultural Program, a project for agricultural modernization in which the Rockefeller Foundation was involved.